Analysis of experiment and calculation of the threaded joints under tension and cyclic bending/Tempiamų ir cikliškai lenkiamų srieginų jungčių bandymų ir skaičiavimų analizė - Krenevičius, Algimantas; Stupak, Marijonas (Journal of Civil Engineering and Management, 1999)
The effect of individual elements of the system “bolt-nut” under tension and bending on the cyclic strength is a complicated and insufficiently clear subject. The data presented in the works of the laboratories of strength mechanics and those of the present authors have been obtained when the ratio of bending and tension stress caused by eccentrically applied tension force was from 0 to 1.5. If stresses caused by bending account for 0.25 σy of tension stresses, the strength to low-cycle fatigue somewhat increases. When σ m = 1.5 σn , the decrease in longevity is observed. The results obtained, however, differ insignificantly from the longevity of threaded joints under cyclic tension as long as bending stresses do not exceed 0.5 σy . A comprehensive experimental study of these problems and the analysis are presented in the works of the present authors. One of the main factors determining the cyclic strength of the system “bolt-nut” is the distribution of internal resultants. The distribution of internal resultants after the threaded joint has been tightened up to σt = 0.6σy corresponds to the general rule which is characteristic of joints under tension. During the first stress cycle due to bending deformations in the cavity of turns of the threads also correspond to the general rule of internal resultant distribution of joints under tension in the layers under tension. In layers under compression, the general effect of tightening and the nut distort the generally accepted laws. The analysis of the formation of the crack and its propagation showed there can be either a single or double crack. When the crack reaches the critical size, the remaining part fractures mostly on account of the deformation energy which was accumulated when stretching the stud, whereas the cyclic propagation of the crack takes place due to bending deformations. Under fluctuating loads threaded joints loosen. Therefore tightness of a vessel subject to high pressure may be lost or the maintenance regime of some device may be disturbed. Due to crushing of contacting surfaces of transmission parts and the thread, spontaneous turn of the nut, plastic deformations in the thread and transmission parts, tightening of the bolt and tightness of transmissions parts may decrease. Studs of demountable joints of energy devices are calculated in accordance with the norms of the Russian Federation and the ASME code. The calculation methods coincide in essence, they are based on similar marginal states. Nevertheless, there exist some differences. The article gives a comparison of some calculating rules for low cycle fracture resistance of the threaded joints. Article in Lithuanian. First Published Online: 26 Jul 2012